Draft Annual Plan, Assam 1965-66, Government of Assam - Planning Commission (Planning Commission, 1965)
The Third Five Year Plan of Assam, as approved by the Planning Commission, entails a total outlay of Rs.120.00 crores. For 1961-62, a total outlay of Rs.17.40 crores was approved by the Planning Commission, against which an expenditure of Rs.17.78 crores was incurred. For 1962-63 a total outlay of Rs.*4224 crores was approved by the Planning Commission, made up of Rs.20.40 crores under the General Plan, an accelerated central assistance of its.3.00 crores for Power Programme and an additional allocation of Rs,1.02 crores for additional Flood Control schemes. Ah expenditure of Rs. 24.58/was incurred. For 1963-64 under the General Plan, a total outlay of Rs.29.50 crores was approved by the Planning Commission including an additional central assistance of Rs.8.00 crores for Power and Flood Control. In addition, a further amount of ks.50.00 lakhs was allocated for the Mizo District Special Programme. the whole amount has, by and large, been spent during the year. For 1964-65 a total outlay of the order of Rs.37 crores was recommended by the various forking Groups. After protracted correspondence and discussions with the Planning Commission, the total outlay has been reduced to Rs. 30.90 crores, including the special assistance of Rs. 50.00 lakhs for the Mizo District Special Programme. Various Heads of Development have since applied for additional allocations and it is likely that this amount may be exceeded during the year.
Draft Annual Plan, Assam 1965-66
Government of Assam